MOTHER'S EXPERIENCE ABOUT BABY MASSAGE IN SUMBEREJO VILLAGE, TRUCUK DISTRICT, BOJONEGORO REGENCY: A QUALITATIVE RESEARCH - Ainul Mufidah; Devi Endah Saraswati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: sage is a form of touch therapy that functions as an important treatment technique that has been known for a long time. In the community, the role of baby massage is still held by traditional birth attendants. Even though baby massage has great benefits for babies, many mothers don't massage their babies independently. The implementation of baby massage is done when their baby is sick or fussy, and as a routine for baby care after birth. Objectives: The purpose of this study was to describe the mother's experience about massaging her baby in Sumberejo Village, Trucuk District, Bojonegoro Regency. Methods: The design in this study uses qualitative research. The selected participants are mothers who have toddlers under the age of 1 year with a total of 10 participants. Participants were taken using purposive sampling technique. Location and Time The research was conducted in the village of Sumberejo, Trucuk District, Bojonegoro Regency. The time of the study was carried out in May-July 2021. The research instrument used in this study was an interview result sheet. Results: Participants in this study amounted to 10 people who were selected based on inclusion criteria. There are 5 themes that have been concluded, namely (1) an overview of baby massage (2) when the baby should be massaged (3) where the mother massages the baby (4) the baby's response after being massaged (5) how often the mother massages her baby. Conclusion: The results showed that more mothers massaged their babies to traditional birth attendants than to professionals and the baby's response after massage was more comfortable and less fussy.